2010
DOI: 10.1007/s00417-010-1385-y
|View full text |Cite
|
Sign up to set email alerts
|

Capsule excision and Ologen™ implantation for revision after glaucoma drainage device surgery

Abstract: Although our study has the limitations of small sample size and observational study design, it shows that further investigation is warranted into the potential of Ologen in revision surgery after GDD implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 16 publications
(30 reference statements)
0
19
0
3
Order By: Relevance
“…Ologen only functions as a wound modulator and does not have any antifibrotic properties to counter the scarring response. However,in previous human studies, Ologen implants used along with deep sclerectomy enhanced the success rates when compared to deep sclerectomy [13], [34]. Future randomized, controlled trials should help determine its place in glaucoma surgery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ologen only functions as a wound modulator and does not have any antifibrotic properties to counter the scarring response. However,in previous human studies, Ologen implants used along with deep sclerectomy enhanced the success rates when compared to deep sclerectomy [13], [34]. Future randomized, controlled trials should help determine its place in glaucoma surgery.…”
Section: Discussionmentioning
confidence: 98%
“…It is a disc-shaped porcine-derived biodegradable collagen matrix that has been developed to prevent excessive scarring after trabeculectomy [2], [11]. When inserted under the conjunctiva at the time of trabeculectomy, it not only acts as a reservoir but also helps to separate mechanically the conjunctiva and episcleral surface and prevent adhesions between them [12], [13]. Recently, many comparative controlled trials have compared the efficacy and tolerability of trabeculectomy augmented with Ologen versus trabeculectomy plus MMC, but the results are not completely consistent.…”
Section: Introductionmentioning
confidence: 99%
“…[1516] They have been used along with deep sclerectomy with better long term success,[1718] and have been used as a spacer following capsule excision after failed GDD surgery. [23]…”
Section: Discussionmentioning
confidence: 99%
“…Analyses with the further advanced CGMs of the second generation (atelocollagen matrices) in revision surgery after failed Baerveldt drainage device surgery revealed supplementary OLO implantation to be a safe method potentially increasing the results in revision surgery of glaucoma drainage devices compared to revision without OLO as a placeholder [22]. Furthermore, two prospective studies using the CGM of the second generation for augmentation of trabeculectomy showed no significant difference compared to the MMC study group (0.2 mg/ml for 2 min) in terms of postoperative success rates [23,24].…”
Section: Discussionmentioning
confidence: 99%